Characteristics of Ferrite-Rich Portland Cement: Comparison With Ordinary Portland Cement - Elakneswaran, Yogarajah; Noguchi, Natsumi; Matumoto, Kazuki; Morinaga, Yuka; Chabayashi, Takashi; Kato, Hiroyoshi; Nawa, Toyoharu (Frontiers in Materials, 2019)
The cement industry is an energy-intensive industry, and improving the energy efficiency of cement has become necessary to reduce its carbon footprint and to compete in the global market. Clinker production consumes more than 90% of the total energy used in the cement industry. Therefore, a reduction in the burning temperature of the cement clinker can reduce the energy consumption; however, it alters the mineralogy of the clinker composition. Ferrite-rich Portland cement can be produced by lowering the burning temperature by approximately 100 ºC (i.e., at 1350 ºC), which can reduce the energy consumption by approximately 5% in comparison with ordinary Portland cement (OPC) clinker. In this study, the hydration reaction and properties of the ferrite-rich Portland cement were examined by experimental techniques and thermodynamic modelling approach, and the results were compared with that of OPC. The produced ferrite-rich cement has almost twice the amount of ferrite phase and half the amount of belite phase contents present in the OPC. The hydration reaction and the composition of hydrates were studied by the X-ray diffraction (XRD)/Rietveld analysis. The different proportions of the ferrite and belite phases in ferrite-rich cement change their hydration reaction from that of the OPC, but not the total hydration of cement. The XRD results reveal similar phases in both the cements, and the analysis could not identify the new phases formed in the ferrite-rich cement. An equal degree of hydration and quantified hydrates at the early age results in almost identical initial and final setting times in both the cements. The ferrite-rich cement demonstrates a high early strength and relatively slower strength development; however, it can develop adequate strength at 28 days. The thermodynamic model predicts the hydration of ferrite-rich cement and shows comparatively high amount of Fe-containing phases, mainly Fe-ettringite and Fe-siliceous hydrogarnet. Model predictions of the hydrates compositions agreed with the experimental results, and a relationship between the predicted total porosity and the measured compressive strength was derived.